A Novel Efficient Sine Wave Inverter with Custom Programmed PWM and Intelligent Control - Haider, A. S.; Naz, A.; Akhter, F.; Azhar, W.; Mehmood, R. (Engineering, Technology & Applied Science Research, 2016)
This article presents an efficient design of a pure sine wave inverter which results in an electronic design with reduced losses. The proposed design incorporates the generation of custom programmed pulse width modulation (CPPWM) waveforms; the gate drive signals that are customized for the harmonic elimination from the output voltage, maximizing the fundamental component and resulting in an efficient electronic circuit design as compared to the traditional techniques in terms of the switching losses and the filtering energy losses. The CPPWM signals are digitally programmed in a micro-controller. The inverter realization is followed by an intelligent compensator design for the regulation of output voltage amplitude. The proposed algorithm self-adjusts its parameters in response to the load current and voltage amplitude variations hence resulting in an improved performance. The simulation results of the control algorithm are presented. The experimental validation of the theoretically investigated controller is also presented by implementing a discrete time realization of the control algorithm using digital controller interfaced in real time with MATLAB®/Simulink®. The hardware results are elucidated. The feasibility of the proposed controller is theoretically and experimentally verified by its efficiency compared to the classical techniques, the available tunable parameters in the controller structure and the immense flexibility in the attainable closed loop dynamics.